Spatial and compositional pattern of alpine treeline, Glacier National Park, Montana - Allen, T R; Walsh, Stephen J (American Society for Photogrammetry and Remote Sensing, 1996)
This study sought to quantify the complex patterns of alpine treeline across an extensive area of Glacier National Park, Montana. Satellite image classification, digital terrain modeling, and geographic information system (GIS) measurements of landscape structure provided important tools for the analysis. The study area was topographically partitioned into watersheds and hillslope units in which to measure treeline patterns. Cluster analysis of selected spatial and compositional pattern metrics was used to infer major alpine treeline forms. Six significant treeline types were differentiated using patch richness, contagion, contrast, number of patches, fractal dimension, relative edge density, and forest-tundra juxtaposition. Clusters were validated using split-sample replication and discriminant analysis. Patterns were found to differ among types of terrain, affirming hypothesized sensitivities to topoclimatic gradients, natural disturbances, and geologic substrate.